Kajian pengolahan air limbah laundry dengan metode adsorpsi karbon aktif serta pengaruhnya terhadap pertumbuhan azolla - Fanty Eka Adiastuti; Miseri Roeslan Afany (Jurnal Ilmu Tanah dan Air, 2018)
Study of Laundry Wastewater Treatment using Activated Carbon Adsorption Method and Its Effects on Azolla Growth (Fanty Eka Adiastuti, Yanisworo Wijaya Ratih, and Miseri Roeslan Afany): Recently, industrial laundry has been increasing rapidly, however generally the waste water of loundry industries were dumped directly to the environment without any treatment.. The purpose of the research is to study pollutants decrease of laundry industrial wastewater by using activated carbon and to evaluate the loundry wastewater treated be used for Azolla cultivation. This research applied 4 treatments that are application of activated carbon with 3 replications using Completely Randomize Design (CRD). The treatment consists of 0g, 5g, 10g, and 15 g of activated carbon which was added in one litre of laundry wastewater. The parameters which were analysis were pH, detergent and P content, also BOD and COD value. The next step is the use of loundry wastewater treated for Azolla cultivation. Azolla biomass was being observed in every 5 days for 20 days. The results showed that the use of 5g/L activated carbon on laundry wastewater increases significantly levels of phosphate, and decreases significantly of detergent content, BOD and COD value. Azolla sp. has not able to grow on Azolla sp. has the ability to grow on the activated carbon application of 5g/L and their growth was not significantly different from 10g/L and 15g/L treatment.